Pemberdayaan Umkm Halal Melalui Pendekatan Ekosistem Kolaboratif Di Kecamatan Tuah Madani Kota Pekanbaru - Umi Rachmah Damayanti; Ade Ria Nirmala; Ratna Nurani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The growth of the global halal industry presents significant opportunities for Indonesia as the country with the world’s largest Muslim population. However, halal Micro, Small, and Medium Enterprises (MSMEs) still face several challenges, including low halal certification literacy, limited access to Islamic financing, weak business digitalization, and minimal implementation of sustainability principles. This community service program aimed to strengthen halal MSMEs through a collaborative ecosystem approach involving universities, local government, and Islamic financial institutions. The program was conducted in Tuah Madani District, Pekanbaru City, involving 38 MSMEs in the food and beverage sector. The implementation methods included socialization, training, mentoring, monitoring, and evaluation. The results showed an increase in halal certification understanding from 52% to 84%, 55% of MSMEs initiated halal certification processes, 45% accessed Islamic financing, and 66% adopted digital financial recording systems. In addition, the program encouraged the use of environmentally friendly packaging and established a local halal MSME forum. This activity produced a sustainable collaborative empowerment model that has the potential to be replicated in other regions. Keywords: Halal Industry, Msmes, Islamic Financing, Digitalization, Green Economy